2013
DOI: 10.1016/j.bbamcr.2013.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Anoikis molecular pathways and its role in cancer progression

Abstract: Anoikis is a programmed cell death induced upon cell detachment from extracellular matrix, behaving as a critical mechanism in preventing adherent-independent cell growth and attachment to an inappropriate matrix, thus avoiding colonizing of distant organs. As anchorage-independent growth and epithelial-mesenchymal transition, two features associated with anoikis resistance, are vital steps during cancer progression and metastatic colonization, the ability of cancer cells to resist anoikis has now attracted ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
856
1
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 948 publications
(879 citation statements)
references
References 260 publications
11
856
1
11
Order By: Relevance
“…A indução da cascata de morte celular ocorre através da interação de duas vias apoptóticas, ou seja, a via das mitocôndrias (via intrínseca) ou a ativação dos receptores de morte da superfície celular (via extrínseca). As proteínas da família BCL-2 são os principais atuantes em ambas as vias (PAOLI et al 2013).…”
Section: Catástrofe Mitóticaunclassified
See 1 more Smart Citation
“…A indução da cascata de morte celular ocorre através da interação de duas vias apoptóticas, ou seja, a via das mitocôndrias (via intrínseca) ou a ativação dos receptores de morte da superfície celular (via extrínseca). As proteínas da família BCL-2 são os principais atuantes em ambas as vias (PAOLI et al 2013).…”
Section: Catástrofe Mitóticaunclassified
“…As células tumorais desenvolvem rapidamente vários mecanismos para resistir à anoikis, espalhando metástases para órgãos distantes. Essas células buscam a resistência por diferentes modos: promovendo mudança específica em suas integrinas, impedindo a ligação dos receptores e adaptando-se ao sítio metastático; realizando a transição do epitélio mesenquimal; ativando uma cascata pró-sobrevivência a fatores intrínsecos e ambientais; e ainda, desregulamentando e adaptando o metabolismo, principalmente pela realização da autofagia (PAOLI et al 2013). …”
Section: Catástrofe Mitóticaunclassified
“…Studies have shown that when cells detach from the matrix and become aggregated, the cells can escape anoikis by intercellular signaling, which mimics cell-matrix signal transduction (Ivanova et al, 2013;Paoli et al, 2013). Aggregation is also believed to enhance their resistance to chemotherapeutic drugs.…”
Section: Correlation Between E-cadherin-regulated Cell Adhesion and Hmentioning
confidence: 99%
“…HIF1α also induces angiopoietin-like-4 (ANGPTL4), a secreted protein essential for tumor growth and resistance to anoikis in GC cells [44] . Cancer cells develop anoikis resistance via several mechanisms, including changes in integrin repertoire expression, induction of EMT, oncogene activation, and adaption of their metabolism [45][46][47] . In gastrointestinal cancers, the PI3K/Akt [48][49][50] and PTEN/PI3K/NF-κB/FAK pathways [51,52] are involved in the formation of PD and anoikis resistance.…”
Section: Cell Survival In the Microenvironment Of The Peritoneal Cavitymentioning
confidence: 99%